2021
DOI: 10.1002/cb.1974
|View full text |Cite
|
Sign up to set email alerts
|

The effect of AI quality on customer experience and brand relationship

Abstract: Although Artificial Intelligence (AI) has been gradually introduced to various industries, research on customer attitudes and behavior toward the use of AI is still in its infancy. Underpinned by flow theory and social identity theory, the current research aims to examine the influence of AI on the customer experience of flow, customer‐brand identification and customer advocacy. In addition, it is suggested that employee responsiveness moderates the effect of AI quality on flow and customer‐brand identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 67 publications
(120 reference statements)
2
32
0
1
Order By: Relevance
“…Thus, this study adds value to the literature related to Gen Z. In addition, this study contributes to the service research by clarifying the predictive power of AI marketing efforts on brand preference (Nguyen et al 2021) and pinpointing the dimensions of AI marketing efforts that affect brand experience and brand preference. It also provides insights to academics who are interested in understanding the role of AI in consumer behavior and decision making.…”
Section: Theoretical Implicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, this study adds value to the literature related to Gen Z. In addition, this study contributes to the service research by clarifying the predictive power of AI marketing efforts on brand preference (Nguyen et al 2021) and pinpointing the dimensions of AI marketing efforts that affect brand experience and brand preference. It also provides insights to academics who are interested in understanding the role of AI in consumer behavior and decision making.…”
Section: Theoretical Implicationsmentioning
confidence: 79%
“…The literature has suggested that AI marketing efforts affect the customer–brand relationship (Nguyen et al 2021 ). When AI quality is high, customers tend to be satisfied with AI services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High service quality can enhance customer satisfaction and loyalty. AI quality has also been emphasized in previous studies (Ashfaq et al, 2020;Nguyen et al, 2022;Sung et al, 2021). For example, it has been found that mixed reality immersion and enjoyment mediate the relationship between AI quality in mixed reality and customers' behavioral intentions (Sung et al, 2021).…”
Section: Service Qualitymentioning
confidence: 88%
“…Importantly, competence entails a significant degree of agent flexibility, both in the moment and diachronically, especially in service situations that require the kind of adaptiveness needed to face sudden environmental changes or outcome failures (Miracchi, 2019). Moreover, the perception of an autonomous technology performing the promised service accurately represents an important informational cue for inferring its functional value (Habel et al, 2017; Nguyen et al, 2021). In other words, if customers know that an AV provides an error free and timely service, they will perceive the AV service to be fulfilling their needs.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%